Effect of fertilizer and stover management on productivity and soil fertility in chickpea (Cicer arietinum)-maize (Zea mays) cropping system - Ahlawat, I.P.S; Gangaiah, B; Singh, Om Pal (The Indian Journal of Agricultural Sciences, 2005)
A field experiment was conducted at New Delhi during 1995-99 to study the effect of fertilizers including biofertilizers and stover management practices on productivity and soil fertility in chickpea (Cicer arietinum L.)-maize (Zea mays L.) cropping system. The results indicated that the yield of chickpea remained unaffected by fertilizer treatments. The yield of miaize increased significantly wiih 100% recommended dose of fertilizer (120,60,40 and 5 kg/ha ofN3, P2,O5,K2O and Zn) over the control (no fertilizer) and biofertilizers. The total productivity in terms of chickpea equivalent yield was the highest with 100% recommended dose of fertilizer to both the crops (3.27 tonnes/ha). Maize stover incorporation recorded markedly higher chickpea yield over chickpea stover and no stover incorporation. Application of stover of both crops or of either of the crops being on par recorded higher chickpea equivalent yield (3.10 tonnes/ha) over no stover incorporation. Stover application, however, had greater impact on chickpea equivalent yield when no fertilizers were applied. Maize stover incorporation recorded the highest chickpea equivalent yield (3.46 tonnes/ha) when maize received 100% recommended dose of fertilizer. The organic carbon content of soil increased with 100% recommended dose of fertilizer and incorporation of stover of both the crops.